EFFECT OF ETHNO-MATHEMATICS AND CONVENTIONAL TEACHING APPROACHES ON STUDENTS’ ACHIEVEMENT, INTEREST AND RETENTION IN GEOMETRY IN SELECTED SECONDARY SCHOOLS IN MAKURDI METROPOLIS, BENUE STATE, NIGERIA - Adamu, Garba (IJRDO -JOURNAL OF MATHEMATICS, 2022)
This study examine the effect of ethno-mathematics and conventional teaching approaches on students’ achievement, interest and retention in geometry in selected secondary schools in Makurdi metropolis, Benue State, Nigeria. Quasi experimental research design and survey research design which follows quantitative methodology were adopted for the study. The sample of 270 respondents was used for the study. The researcher used primary data obtained by the use of a structured questionnaire. The data collected were analyzed using inferential statistics such as simple linear regression and analysis of covariance (ANCOVA). The result of the study indicates that a negative effect was established between ethno-mathematics teaching approach and students’ achievement in geometry. The effect is not statistically significant (p>0.05) and the effect is in line with a priori expectation. For the second and third model of the study, ethnomathematics teaching approach have a positive and significant effects (p<0.05) on students’ interest and students' retention in geometry in selected secondary schools in Makurdi Metropolis, Benue State, Nigeria. Male had less achievement than female student taught geometry using of ethno-mathematics teaching approach than the conventional teaching approach and this difference is statistically significant. Also, female had more interest in geometry taught using ethno-mathematics teaching approach than the conventional approach and the difference is statistically significant. For the third model of the study, there are difference in retention between male and female students taught geometry using of ethno-mathematics teaching approach than those taught using the conventional teaching approach s and the difference is statistically significant. It is concluded that ethnomathematics is beneficial in the teaching of geometry as it has a positive effect on interest and retention. It is recommended among others that Mathematics instruction in general should be handled in such a way that students are actively involved in the learning processes, enabling them to see Mathematics as a natural extension of their daily life activities, hence improving students' interest and retention in geometry in the study area.